2021
DOI: 10.1001/jamapediatrics.2020.5320
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Elimination Diet and Symptoms of Cow’s Milk Allergy in Breastfed Infants—Reply

Abstract: In Reply In our article published in May 2020, we highlighted the need for innovative ways of delivering education, health, and social services owing to the disruptions caused by the coronavirus disease 2019 COVID-19 pandemic. 1 As the the pandemic progresses, many school districts have implemented virtual learning during the fall semester. 2 We appreciate Wong's identification of a novel way to deliver preschool and early intervention services to children and directly engage parents through employment. Traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…However, it has not been well-documented yet whether they can trigger allergic sensitization in infants. The latest systematic reviews on this topic [ 10 , 11 , 12 , 13 , 14 ] as well as the 2019 American Academy of Pediatrics report [ 6 ] concluded that there is a lack of evidence to support maternal dietary restrictions during pregnancy and lactation. After many years of allergen avoidance, new guidelines recommend early exposure of the infants to oral allergens with the goal of inducing regulatory immune responses and generating tolerance to allergens [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has not been well-documented yet whether they can trigger allergic sensitization in infants. The latest systematic reviews on this topic [ 10 , 11 , 12 , 13 , 14 ] as well as the 2019 American Academy of Pediatrics report [ 6 ] concluded that there is a lack of evidence to support maternal dietary restrictions during pregnancy and lactation. After many years of allergen avoidance, new guidelines recommend early exposure of the infants to oral allergens with the goal of inducing regulatory immune responses and generating tolerance to allergens [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, parental‐ and self‐report significantly overestimate the rate of food allergy. For example, a recent review concluded that confirmed milk allergy is 15‐ to 20‐fold less frequent than parentally reported symptoms 4 . Similarly, a European systematic review suggested a self‐reported prevalence between 13.1% and 19.9%, with serum IgE sensitization of 16.6% and skin testing of 5.7%, with only 0.8% based on oral food challenge (OFC).…”
Section: New Trends In Food Allergy Prevalencementioning
confidence: 99%
“…For example, a recent review concluded that confirmed milk allergy is 15-to 20-fold less frequent than parentally reported symptoms. 4 Similarly, a European systematic review suggested a self-reported prevalence between 13.1% and 19.9%, with serum IgE sensitization of 16.6% and skin testing of 5.7%, with only 0.8% based on oral food challenge (OFC). Lipid transfer protein allergy has emerged as the most common cause of primary food allergy and food-induced anaphylaxis in older children and adults residing in Southern European countries (Mediterranean and Atlantic areas).…”
Section: Ne W Trends In Food Allergy Pre Valen Cementioning
confidence: 99%